The EAF model as a tool for company wage fund management - Jurij Renkas ,; Kacper Rosa , (SPC Journal of Social Sciences, 2024)
This article aims to address recent debates on wage increases, the flattening wage structure, and effective labor remuneration systems by developing a model that assesses real wage levels, human capital utilization, and management quality within a company. Using mixed meth-ods, including a literature review and a case study of Komfort-Eko Ltd., the study highlights the importance of the constant a =0.08 [1/year] in analyzing wage systems. Key findings led to the development of the Economic Activity Function (EAF), which estimates the Management Index M, the Labour Productivity Index Q, and the overall wage level based on financial data, providing a new framework for evaluating management performance and forecasting future remuneration levels. The EAF model enables simulation of financial scenarios, aiding policymakers and managers in optimizing remuneration strategies and enhancing employee motivation systems. This study contrib-utes to human resource management literature by deriving the Management Index M and refining a model for labor productivity measure-ment, supported by the theoretical role of a constant parameter, while using the EAF to forecast future wage funds, including bonuses.